Pencegahan Seks Bebas Pada Remaja Di Era Digitalisasi Di Smp Negeri 1 Pakis, Magelang, Jawa Tengah - Ida Indriani; Imram Radne Rimba Putri; Faza Chumaida (Bangun Desa: Jurnal Pengabdian Masyarakat, 2023)
Free sex is sexual relations that are carried out outside of marriage, either consensual or in the world of prostitution, such as intimate peace, making out, to having sexual contact, but this behavior is considered not in accordance with the norm because adolescents do not have experience about sexuality. In Indonesia, there are around 4.5% of male youth and 0.7% of female adolescents aged 15-19 who admit to having had premarital sex. In adolescents aged 15-19 years, the largest proportion is for the first time at the age of 15-17 years. Approximately 33.3% of female adolescents and 34.5% of male adolescents aged 15-19 years began to become aware when they were not yet 15 years old. The record for the cumulative number of sufferers of Human Immunodeficiency Virus (HIV) and Acquired Immune Deficiency Syndrome (AIDS) until 2017 by the Magelang City AIDS Commission (KPA) was 126 sufferers. Consists of 93 HIV, 33 AIDS and 26 of them died. This community service activity has the aim of providing health education related to the importance of the dangers of free sex in adolescents and prevention of free sex in this digitalization era. The activity was attended by 35 students of SMP Negeri 1 Pakis. The method used in this community service activity is the joint discussion technique. The results of measuring the prevention of free sex in adolescents in the digitalization era before and after the socialization was given, it was found that around 95% of participants understood the prevention of free sex in adolescents in the digitalization era Keywords: Teenager, Free Sex, Digitalization